2008
DOI: 10.1055/s-2008-1079256
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alternatively Spliced Tissue Factor in Pancreatic Cancer Growth and Angiogenesis

Abstract: Increased tissue factor (TF) expression is observed in many types of cancer, associated with more aggressive disease, and in thrombosis. The mechanism by which TF promotes tumor growth remains unclear. Anticoagulation has been shown to result in a trend toward improved survival; no direct antitumor effect has been shown in cancer patients. Alternatively spliced tissue factor (asTF) was recently described, in which exon 5 is deleted. Because of a frame-shift in exon 6, the transmembrane and cytoplasmic domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
0
23
1
2
Order By: Relevance
“…asTF is a non-membrane anchored molecule of 27kDa that, while retaining most of the contact sites for coagulation factor VIIa, lacks large portions of an exosite for macromolecular substrates 18 . As a result, asTF has no appreciable procoagulant activity and it is believed to play a more prominent role in promoting angiogenesis 19, 20 . Unlike fl-TF, asTF exhibits angiogenic activity via integrin ligation and activation of Focal Adhesion Kinase (FAK) in a factor VIIa and Protease-Activated Receptor-2 (PAR-2) independent manner 19, 21–23 .…”
Section: Introductionmentioning
confidence: 99%
“…asTF is a non-membrane anchored molecule of 27kDa that, while retaining most of the contact sites for coagulation factor VIIa, lacks large portions of an exosite for macromolecular substrates 18 . As a result, asTF has no appreciable procoagulant activity and it is believed to play a more prominent role in promoting angiogenesis 19, 20 . Unlike fl-TF, asTF exhibits angiogenic activity via integrin ligation and activation of Focal Adhesion Kinase (FAK) in a factor VIIa and Protease-Activated Receptor-2 (PAR-2) independent manner 19, 21–23 .…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Recently, alternatively spliced TF has been found to promote tumor growth and to be a proangiogenic factor. 32,33 Alternatively spliced TF, unlike full-length TF, does not affect angiogenesis through proteinactivated receptor-dependent pathways but relies on integrin ligation. 34 We also investigated how TF can directly regulate angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…asTF is therefore soluble and has been detected both in the blood circulation and in various normal and cancerous tissues [3][4][5][6][7]. Recent studies have proved that asTF does not play a significant role during coagulation [8,9] but is likely essential during angiogenesis associated with the development of cancer [4,10]. We recently demonstrated that high tumor TF expression in non-small cell lung cancer (NSCLC) was associated with reduced survival of affected patients and that overexpression of TF was linked to oncogenic events, such as KRAS, p53 and PTEN mutations [11,12].…”
mentioning
confidence: 99%